“The Long Road of Reconciliation”: The Church of Sweden’s Performative Apology to the Sámi People - Gindt, Dirk (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2023)
Grounded in performance theories and Indigenous methodologies, this essay focuses on the 2021 solemn service in Uppsala Cathedral, when the Church of Sweden apologized for its historical complicity in the colonization of Sápmi. The essay discusses key rhetorical features of the Archbishop’s apology and analyses how the service incorporated Sámi visual, material, oral, and performance cultures. Of specific interest are five Sámi testimonies about settler colonialism and artist Anders Sunna’s redesign of the sanctuary. To tease out the contextual specificities (and limitations) of the apology and situate it as part of unfolding decolonial processes across the circumpolar North, the essay draws selective comparisons to Canada’s Truth and Reconciliation Commission and former Prime Minister Stephen Harper’s 2008 formal apology to First Nations, Inuit, and Métis Peoples.